The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/jora.12338
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Relations of Economic Hardship and Effortful Control to Active Coping in Latino Youth

Abstract: How Latino youth cope with stressors may have implications for their adjustment. We examined how a temperamental characteristic (effortful control) and a contextual factor (economic hardship) were associated with Latino youth's coping. Individual differences in effortful control, a core facet of self-regulation, may contribute to coping as effortful control is consistently linked to adaptive behaviors during adolescence. We examined relations of effortful control and economic hardship to active coping in a sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 88 publications
(140 reference statements)
2
18
0
Order By: Relevance
“…Our work was consistent with prior research finding effortful control serves to protect Latino youth from depressive problems (Loukas & Roalson, 2006; Taylor et al, 2018; Taylor, Widaman, & Robins, 2018; Valiente et al, 2009), although given that our findings were only significant for T1, we cannot show directionality. Researchers have found that effortful control and coping strategies are linked in Latino children in middle childhood and early adolescence (Taylor, Widaman, & Robins, 2018; Valiente et al, 2009), and that higher effortful control negatively predicts Latino children’s internalizing and externalizing problems (Loukas & Roalson, 2006; Taylor et al, 2018; Valiente et al, 2009). Researchers have also hypothesized that regulatory traits such as effortful control could provide a promising index of adolescent resilience (Dishion & Connell, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our work was consistent with prior research finding effortful control serves to protect Latino youth from depressive problems (Loukas & Roalson, 2006; Taylor et al, 2018; Taylor, Widaman, & Robins, 2018; Valiente et al, 2009), although given that our findings were only significant for T1, we cannot show directionality. Researchers have found that effortful control and coping strategies are linked in Latino children in middle childhood and early adolescence (Taylor, Widaman, & Robins, 2018; Valiente et al, 2009), and that higher effortful control negatively predicts Latino children’s internalizing and externalizing problems (Loukas & Roalson, 2006; Taylor et al, 2018; Valiente et al, 2009). Researchers have also hypothesized that regulatory traits such as effortful control could provide a promising index of adolescent resilience (Dishion & Connell, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Overall, our study suggests that a higher CAR may be adaptive in the short term for Latino preadolescents perhaps by promoting flexible responding to their environments through effortful control, an aspect of temperament known to facilitate positive adjustment and lower levels of internalizing problems in this population (Loukas & Roalson, 2006; Taylor et al, 2018; Taylor, Widaman, & Robins, 2018). Importantly, our study focused on factors that are related to well-being in Latino youth, rather than solely documenting potential vulnerabilities and risks.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Nine published papers have used data from the California Families Project (CFP) to examine temperament measured via the EATQ-R(Atherton, Lawson, Ferrer, & Robins, 2020; Atherton, Lawson, & Robins, in press;Atherton, Schofield, Sitka, Conger, & Robins, 2016;Atherton, Tackett, Ferrer, & Robins, 2017;Atherton, Zheng, Bleidorn, Robins, 2019;Clark, Donnellan, Conger, & Robins, 2015; Clark, Donnellan, & Robins, 2018;Robins, Donnellan, Widaman, & Conger, 2010;Taylor, Widaman, Robins, 2018). No previous CFP publications have examined suicidal ideation, plans, or attempts.…”
mentioning
confidence: 99%